Pengembangan Media ICT Berbasis Chemoedutainment Berupa Chemblocks Games Untuk Memfasilitasi Pembelajaran di Masa Pandemi COVID-19 - Nillam Puspitaningrum; Munasprianto Ramli; Luki Yunita (Universitas Negeri Padang, 2021)
The use of ICT learning media is needed to support the learning process. This is due to the implementation of the 2013 curriculum, technological developments in the era of the industrial revolution 4.0, and the COVID-19 pandemic. One example of ICT media that is in great demand by students is learning multimedia in the form of educational games with the Chemoedutainment method. This study aims to produce an educational game application called Chemblocks Games based on Chemoedutainment on chemical bonding materials. The subjects in this study were expert validators, teachers, and students. This study uses the TSRD model R and D method, which consists of the following stages Pre development, Development, and Post Development. The instruments used are a mix of teacher needs analysis interviews, student needs analysis questionnaires, validation sheets, also teacher and student response questionnaires. Validation data processing techniques and response questionnaires use a Likert scale. Data analysis was carried out by converting the results of the Likert scale points into percentages. Chemblocks Games received an assessment from material experts of 88.61 percent, media experts of 83.5 percent and teacher participant test assessments of 94 percent. So the Chemblocks Games product is in the very decent category. Based on the results of the student response questionnaire in the limited test, the percentage obtained was 84.5 percent in the material aspect, 86.5 percent in the language aspect, and 87 percent in the attractiveness aspect. So the students response to the Chemblock Games application is in the Very Good category.